Investigating the Potential of Fluorescent Fingerprint Powders as a Marker for Blow Fly Larvae (Diptera: Calliphoridae)1. Issue 3 (20th February 2015) - Rosati, Jennifer Y.; Robinson, Scott D.; Devine, Richard
Abstract Four fluorescent fingerprint powders (RedWop™, GreenWop™, Basic Yellow™, and Yellow Powder™) were evaluated as a marker for blow fly larvae. Administration methods included ingestion (high vs. low concentration) or topical. Ingestion of high concentrations of Basic Yellow™ and RedWop™ caused higher larval mortality. Basic Yellow™ delayed development and adult emergence while RedWop™ and Yellow Powder™ had a significant effect on particular stages of development, however, emergence time was not altered. Optimal administration is through ingestion at low concentration levels (<10%) or topically, with GreenWop™ demonstrating minimal adverse effects. Optimum wavelength for discrimination between powders was 450 nm. This research can aid in investigative training to increase visibility of larval and pupal blow flies. It can also be used in entomological studies to differentiate between larval blow flies (or other dipteran) species or individuals to further understand complex interactions and behavior during larval development.